Inclusión de harina de sangre sobre los parámetros productivos en pollos de engorde Ross 308 - Peralta Puedmag, Bryan David (2025)
The purpose of the research was to evaluate the productive parameters of Ross 308 broilers by including bovine blood meal in different proportions in their diet. A total of 200 broilers were reared in a completely randomized design, in two stages: Growth stage from day 0 to 21 with commercial feed and completion from day 22 to 42 where the treatments, T0 0%, T1 5%, T2 10%, T3 15% were applied, each treatment formed by 5 repetitions of 10 experimental units each, giving a total of 50 units per treatment. The variables evaluated included: cumulative weight gain, cumulative feed intake, feed conversion, carcass yield, mortality percentage, cost-benefit ratio and degree of pigmentation. The analysis of variance (ANOVA) followed by Tukey's test showed that T1 presented the highest values for accumulated weight gain (2.98 kg), accumulated feed consumption (4.70 kg), carcass yield (79.15%) and cost-benefit (0.59 cents). Similarly, in T1 it was statistically observed that the percentage of mortality was similar to the other treatments, as was the degree of pigmentation. In conclusion, the inclusion of 5% blood meal in the daily diet of Ross 308 broilers significantly improved productive parameters compared to inclusion levels of 10% and 15%, suggesting an alternative in the feeding of Ross 308 broilers.